Pengaruh Terapi Kompres Madu terhadap Penyembuhan Luka Full Thicknes Skin Loss pada Tikus Putih (Rattus Norvegicus) - Dina Zakiyyatul Fuadah; Diana Rachmania; Novita Yudik (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2015)
Wounds require a very effective treatment for example an open wound. Honey compress therapy is one method that can be used for wound healing process. The purpose of this study, to determine the effect of therapy on wound healing using honey compress full thicknes skin loss on Rattus norvegicus.Design for the research is True Experiments using post-test design with control group design. Samples were 18. Sampling using random sampling techniques. The independent variable is the honey compress therapy and the dependent variable is the process of wound healing of full thicknes skin loss. Data were analyzed using the Mann Whitney test (α = 0.05).The results of the statistical test on day 15, p value = 0.004 <α that's meanthere are significant differences between the treatment group and the control group in wound healing of full thicknes skin loss on Rattus norvegicus.Honey compress therapy accelerates wound healing process full thicknes skin loss. It is recommended for people can take advantage of pure honey for wound healing due to the composition of honey that can help the healing process.